Association of foveal avascular zone area withstructural and functional progression in glaucoma patients. Issue 9 (7th April 2021) - Li, Fei; Lin, Fengbin; Gao, Kai; Cheng, Weijing; Song, Yunhe; Liu, Yuhong; Wang, Yu Meng; Lam, Alexander; Tham, Clement C; Cheung, Carol; Zhang, Xiulan; Zangwill, Linda M.
Abstract : Background: To investigate whether quantitative optical coherence tomography angiography (OCTA) metrics of the superficial/deep macular retina and optic disc are associated with glaucoma progression risk. Methods: A total of 238 eyes from 119 patients with open angle glaucoma or ocular hypertension, and no history of systemic hypertension or diabetes mellitus were included. All participants underwent OCTA imaging with a swept-source OCT (DRI-OCT 1, Topcon, Japan). OCTA metrics of superficial capillary plexus (SCP) and deep capillary plexus (DCP) in the macular region, and radial peripapillary capillary network of the optic disc were measured by a customised MATLAB program to obtain foveal avascular zone (FAZ) area, FAZ circularity and capillary density of SCP/DCP, and capillary density of the peripapillary region. Relationships between baseline OCTA metrics, visual field (VF) metrics, intraocular pressure fluctuation and risk of glaucoma progression were analysed with the Cox proportional hazards model. A frailty model was used to adjust for intereye correlation. Results: During a mean follow-up duration of 29.39 months (range 12–56 months), 50, 48 and 16 eyes were determined to have retinal nerve fibre layer (RNFL), ganglion cell-inner plexiform layer (GC-IPL) and VF progression respectively. FAZ area per SD increase at baseline were significantly associated with both RNFL thinning (HR 1.73 95% CI 1.04 to 2.90); p=0.036) and GC-IPL thinning (HR 2.62, 95% CI 1.59 to 4.31; p<0.001), after adjusting for age, axial length and other potential confounding factors. VF progression was associated with age (HR 1.05, 95% CI 1.02 to 1.08; p<0.001) and mean deviation value (HR 0.91, 95% CI 0.84 to 0.98; p=0.010), but not with any OCTA metrics. Conclusion: Enlarged FAZ area measured by OCTA was associated with a higher risk of RNFL and GC-IPL thinning associated with glaucoma, but not with functional deterioration in glaucoma.